Making Advertising Videos To Develop Promotional Media On Tiktok Using The Sony Vegas Application At The Yuni Catering Jember Business - Laela, Sefina Nur; Utomo, Heru (SEAN Institute, 2023)
This study aims to develop promotional media on Tiktok social media Yuni Catering Jember by creating an advertising video that will display one of the products from Yuni Catering Jember and provide more complete information. This study used the type of Action Research which consists of planning, action, observation, and reflection. Data collection methods included observation, interviews, documentation and questionnaires. The research results were obtained from distributing questionnaires to 1 owner, 2 multimedia experts, 2 marketing experts, and 15 potential customers. The Measurements Of design effectiveness used the EPIC Model which consists of 4 dimensions namely empathy, persuasion, impact, and communication. The results of measurement show that the design effectiveness has an average EPIC Rate of 4.35 out of 5. This indicates that respondents strongly agree that the advertising video is feasible and effective as a promotional media for Yuni Catering Jember.